If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + 3t = 22 Solving 2s + 3t = 22 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-3t' to each side of the equation. 2s + 3t + -3t = 22 + -3t Combine like terms: 3t + -3t = 0 2s + 0 = 22 + -3t 2s = 22 + -3t Divide each side by '2'. s = 11 + -1.5t Simplifying s = 11 + -1.5t
| 26=5+3v | | 2=2y-2 | | [4-(5-3(3-5)+2)]+4= | | 7p+8q=29 | | 65X-78Y=3 | | 3p+4q=13 | | u/5-14=27 | | 4x+1=3x-9 | | 3w+12=36 | | -v-10=-6v | | 7-4=-9 | | 27=x/4-11 | | 2y+11=35 | | 7x+6-3x=3x-5 | | 7(y-6)=21 | | -1/3(x-9)=4 | | 0=6.28r^2+1130.4r-14469.12 | | z/9=7 | | 3-5y=-17 | | 3=t/9 | | x^3+19x^2=0 | | 18-a/3=-5 | | (10x-25)/5 | | 0=r^2-112.36 | | x+32-2=20 | | 0=6.28r^2+137.532r-1270.444 | | y/6-3=-12 | | 2(2x+7)=-4(3-2x) | | 8-2x=-8+14 | | 11(w-7)^2/2-20=101 | | 11(w-2/7)^2-20=101 | | 2.40/x=11 |